City-Heat Equity Adaptation Tool (City-HEAT): Multi-objective optimization of environmental modifications and human heat exposure reductions for urban heat adaptation under uncertainty. (February 2023) - Shi, Rui; Hobbs, Benjamin F.; Quinn, Julianne D.; Lempert, Robert; Knopman, Debra
Abstract: Rising global temperatures and the urban heat island effect can amplify heat-related health risks to urban residents. Cities are considering various heat adaptation actions to improve public health, enhance social equity, and cope with future conditions beyond past experience. We present the City-Heat Equity Adaptation Tool (City-HEAT), which suggests optimal investments for mitigating urban heat and reducing health impacts through modifications of built (cool roofs/pavements) and natural (urban afforestation) environments and reductions of people's heat exposure (cooling centers). The optimization considers multiple public health and social objectives under a wide range of future scenarios. An application to Baltimore, MD (USA) demonstrates how City-HEAT can generate Pareto-efficient multi-year heat adaptation plans. We quantify effectiveness-efficiency-equity tradeoffs among alternative plans and show the advantages of flexible decision-making. City-HEAT can be adapted to the natural, built, and social environments of other cities to support their urban heat adaptation planning, recognizing local objectives and uncertainty. Highlights: City-HEAT models the climate/built & natural urban environment/human society nexus . City-HEAT optimizes heat adaptation under deep uncertainty. City-HEAT generates Pareto-efficient multi-decadal adaptation strategies. Effectiveness-efficiency-equity tradeoffs are identified among strategies. Comparison of strategies quantifies advantages of flexibility in decision-making.